Uplift cinema the emergence of African American film and the possibility of black modernity - Field, Allyson Nadia 1976- (Duke University Press, 2015)
The aesthetics of uplift: the Hampton-Tuskegee idea and the possibility of failure -- "To show the industrial progress of the Negro along industrial lines?" : uplift cinema entrepreneurs at Tuskegee Institute, 1909-1913 -- "Pictorial sermons" : the campaign films of Hampton Institute, 1913-1915 -- "A vicious and hurtful play" : the Birth of a Nation and the new era, 1915 -- To "encourage and uplift" : entrepreneurial uplift cinema